2017
DOI: 10.1016/j.msksp.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted body-image and pregnancy-related lumbopelvic pain. A preliminary investigation

Abstract: Self-reported disruption of body-image was significantly greater in pregnant women who were experiencing lumbopelvic pain than those who weren't and the extent of body-image disruption was associated with pain intensity. Only pain related catastrophisation was related to disrupted body-image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 82 publications
5
10
0
1
Order By: Relevance
“…There was no correlation between the FreBAQ-G and the TPD, in contrast to our initial hypothesis. These results were in keeping with Wand et al [ 29 ] who found no correlation between the English version of the FreBAQ and TPD in a sample of 34 pregnant women. This questions the assumption whether both assessments measure the same construct, although previous studies have demonstrated a relationship between body image drawings and tactile acuity in patients with CLBP [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was no correlation between the FreBAQ-G and the TPD, in contrast to our initial hypothesis. These results were in keeping with Wand et al [ 29 ] who found no correlation between the English version of the FreBAQ and TPD in a sample of 34 pregnant women. This questions the assumption whether both assessments measure the same construct, although previous studies have demonstrated a relationship between body image drawings and tactile acuity in patients with CLBP [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…In people with CLBP, the FreBAQ has been associated with a number of clinical characteristics such as pain duration (Pearson correlation ρ = 0.357, p = 0.01) and pain intensity (Spearman’s rho = 0.40, p = 0.004) [ 26 ] though others have found no such relationship [ 28 ]. As a measure of body perception it has demonstrated evidence for known-groups validity (median difference between healthy controls and people with CLBP = 11, Mann-Whitney test, p< 0.001) and reliability (ICC2,1 agreement = 0.652 (95% CI: 0.307 to 0.848),ICC2,1 consistency = 0.667 (95% CI: 0.317 to 0.857) [ 26 ] but did not provide evidence of convergent validity with other body perception measures in a different pain population [ 29 ]. The FreBAQ was recently translated and validated into Japanese (FreBAQ-J) [ 27 ] and Dutch [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the score on the FreBAQ questionnaire in the CP_Pain population was no different from that seen in a matched group with LBP and no CP and very similar to the results of previous investigations that have used the FreBAQ to assess body perception in general LBP populations . This builds on work demonstrating that lumbopelvic self‐perception is impaired in people with LBP compared to matched control groups and extends this finding to include people with LBP and CP.…”
Section: Discussionsupporting
confidence: 84%
“…They also found more perceptual dysfunctions in moderate-disability sub-groups respect to lowdisability patients (median score: 6.5/36 points) and pain free controls (median score: 2/36 points), however there was no statistical significance (respectively, p = 0.282 and p = 0.095; personal communication). Wand et al (2017) instead collected data on pregnancy-related LPP (within the 3rd trimester of pregnancy and not over the 38th week): women with pain referred significantly (p = 0.005) more perceptual dysfunctions than those pain-free (median score: 3.5/36 vs. 1/36), and authors found a significant correlation (p = 0.027) of FreBAQ score with pain intensity (r = 0.378), despite it was not correlated with self-reported disability (p = 0.143).…”
Section: Self-administered Questionnairementioning
confidence: 99%